The process of formation studying motivation as a way to successful professional training of interns-pediatricians - L. V. Kolyubakina; V. S. Khilchevska (Kazimierz Wielki University, 2017)
The paper analyzes results of anonymous questionnaire of interns in pediatrics to assess motivation during the internship.